Recent Advances in Understanding Mammalian Prion Structure: A Mini Review - Terry, Cassandra; Wadsworth, Jonathan D. F. (Frontiers in Molecular Neuroscience, 2019)
Prions are lethal pathogens, which cause fatal neurodegenerative diseases in mammals. They are unique infectious agents and are composed of self-propagating multi-chain assemblies of misfolded host-encoded prion protein (PrP). Understanding prion structure is fundamental to understanding prion disease pathogenesis however to date, the high-resolution structure of authentic ex vivo infectious prions remains unknown. Advances in determining prion structure have been severely impeded by the difficulty in recovering relatively homogeneous prion particles from infected brain and definitively associating infectivity with the PrP assembly state. Recently however, images of highly infectious ex vivo PrP rods that produce prion-strain specific disease phenotypes in mice have been obtained using cryo-electron microscopy and atomic force microscopy. These images have provided the most detailed description of ex vivo mammalian prions reported to date and have established that prions isolated from multiple strains have a common hierarchical structure. Misfolded PrP is assembled into 20 nm wide rods containing two fibres, each with double helical repeating substructure, separated by a characteristic central gap 8–10 nm in width. Irregularly structured material with adhesive properties distinct to that of the fibres is present within the central gap of the rod. Prions are clearly distinguishable from non-infectious recombinant PrP fibrils generated in vitro and from all other propagating protein structures so far described in other neurodegenerative diseases. The basic architecture of mammalian prions appears to be exceptional and fundamental to their lethal pathogenicity.